PREVALENCE OF PAEDIATRIC TUBERCULOSIS AND TUBERCULOSIS-HIV CO-INFECTION IN SELECTED HOSPITALS WITHIN KATSINA METROPOLIS, KATSINA STATE, NIGERIA - Bawa-Sani, Hafsatu Garba; Abdulkadir, Bashir; Ibrahim, M. Abdullah; Ibrahim, O. Rasheed; Umar, F. Mani; Lugga, A. Sani (FUDMA JOURNAL OF SCIENCES, 2025)
Children represent the second highest-risk group for tuberculosis (TB) in Nigeria, with Katsina State recording the highest prevalence (23%) and a notable recent increase of 42%. TB   remains a major opportunistic infection in individuals living with HIV. However, data on paediatric TB and HIV co-infection in Katsina are limited. This study aimed to determine the prevalence of paediatric TB in selected hospitals within Katsina metropolis. A total of 128 children were randomly selected and screened for TB and rifampicin-resistant TB (RR-TB) using the Xpert MTB/RIF Ultra assay. HIV status was assessed using the Determine rapid diagnostic test. Six children tested positive for TB, yielding a prevalence of 4.7%. No cases of RR-TB were detected. The highest prevalence (66.7%) occurred among children aged 5–14 years, with equal distribution between males and females. None of the TB-positive children were co-infected with HIV. Despite existing control efforts, paediatric TB remains a public health concern in the study area, hence the need for strengthened health education, active case finding, and improved access to timely diagnosis and treatment to support TB eradication among children in Katsina.
Keywords: Paediatric Tuberculosis; Mycobacterium/TB Gene Xpert (MTB/RIF)